TSH Levels in Subclinical Hypothyroidism in the 97.5th Percentile of the Population - Laura Pérez-Campos Mayoral; María Teresa Hernández-Huerta; Gabriel Mayoral-Andrade; Eduardo Pérez-Campos Mayoral; Edgar Zenteno; Ruth Martínez-Cruz; Héctor Martínez Ruíz; Margarito Martínez Cruz; Alma Dolores Pérez Santiago; Eduardo Pérez-Campos (International Journal of Endocrinology)
The debate regarding the cutoff point in the treatment of patients with subclinical hypothyroidism (Shypo) is ongoing. Generally, two different groups are identified for treatment by levels of 10 and 20 mIU/L. Nevertheless, the question remains, “what cutoff point should be chosen?” We have written a selective nonsystematic review focused on the 97.5 percentile reference value reported in healthy subjects in a number of countries and observed important disparities, which partly show the challenge of identifying a single cutoff point for those patients needing medication. We identified studies of TSH on the natural history of subclinical hypothyroidism from population-based prospective cohort studies, which follow up patients for several years. The evolution of TSH levels in these patients is variable. Some cases of TSH may return to lower levels at different stages over the years, but others may not, possibly even developing into overt thyroid failure, also variable. We analyzed factors that may explain the normalization of serum TSH levels. In addition, we found that thorough population-based prospective cohort studies following up on TSH levels, thyroid antibodies, and ultrasonography are important in decisions made in the treatment of patients. However, the 97.5 percentile reference value varies in different countries; therefore, an international cutoff point for subclinical hypothyroidism cannot be recommended.